2021
DOI: 10.1113/jp281620
|View full text |Cite
|
Sign up to set email alerts
|

Physiological mechanisms of unexplained (functional) gastrointestinal disorders

Abstract: Functional gastrointestinal disorders (FGIDs) encompass a range of complex conditions with similar clinical characteristics and no overt pathology. Recent recognition of sub‐clinical pathologies in FGIDs, in conjunction with physiological and biochemical abnormalities including increased intestinal permeability, microbial profile alterations, differences in metabolites and extra‐intestinal manifestations of disease, call into question the designation of these conditions as ‘functional’. This is despite signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 204 publications
(200 reference statements)
1
11
0
2
Order By: Relevance
“…Therefore, fatigue may be a consequence of gastrointestinal imbalance, and targeting on specific intestinal bacteria and gut microbial ecosystem modulation may be a worthwhile therapeutic strategy in fatigue management [9,34]. Although such associations between gut microbiota and the MCP are established, the underlying mechanisms by which the microbiota and the host interact remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, fatigue may be a consequence of gastrointestinal imbalance, and targeting on specific intestinal bacteria and gut microbial ecosystem modulation may be a worthwhile therapeutic strategy in fatigue management [9,34]. Although such associations between gut microbiota and the MCP are established, the underlying mechanisms by which the microbiota and the host interact remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The duodenal microenvironment has emerged as an important player in the pathophysiological mechanisms of FD, in which both locally microbial community disorder, host and microbial metabolism and host innate immunity are involved ( 27 ). These imbalances may in part be mediated by specific microbiome-associated metabolites ( 28 ). A recent study showed that the metabolic functional prediction of oral and gastric microbiome based on 16S rRNA sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no consensus regarding the specific differences and mechanisms at play, it is clear that sex differences exist in circadian rhythms and melatonin metabolism ( Cipolla-Neto et al, 2021 ) which may in part explain the higher prevalence of DGBIs in women ( Burns et al, 2021 ). In healthy women, the intrinsic circadian period of melatonin and body temperature are shorter ( Duffy et al, 2011 ) and females also tend to wake up earlier, with morning chronotypes ( Adan and Natale, 2002 ; Cain et al, 2010 ).…”
Section: Melatoninmentioning
confidence: 99%
“…Importantly, over 40% of the global population experience GI symptoms associated with these conditions ( Sperber et al, 2021 ), highlighting the need to better understand the mechanisms underlying symptom onset and chronicity. Further, alterations in immune profiles, microbiota composition and physiology of the GIT are linked to DGBIs ( Burns et al, 2021 ), all of which are associated with chronodisruption and as such, it is likely that altered circadian rhythms are involved in the pathophysiology of these conditions. This review aims to discuss the evidence for circadian abnormalities in DGBIs with a focus on FD and IBS.…”
Section: Introductionmentioning
confidence: 99%